The Sufi Mystical Idiom in Alevi Aşık Poetry: Flexibility, Adaptation and Meaning - Caroline Tee (European Journal of Turkish Studies)
The Alevi tradition in Turkey is characterized by a profoundly mystical religious worldview. Its poetic culture, aşıklık, is heavily influenced by the language and mystical motifs of Persian Sufism. Yet whilst the major precepts of Sufi theology and ritual practice undeniably constitute an important influence on Alevilik, there are areas of its mysticism that are uniquely Alevi. This paper explores the particularities of Alevi mysticism by analyzing the context and meaning of the Sufi poetic idiom in Alevi poetry. The subject is approached through an ethnographic study of the life and poetry of a contemporary Alevi aşık from Erzincan, called Ozan Seyfili, the span of whose life covers the past six decades. It concludes by considering the future prospects for Alevi mysticism as the community codifies and reformulates its traditions in the present day.